The international law of Human trafficking - Gallagher, Anne T. (New York [etc.] Cambridge University Press, 2010)
Although human trafficking has a long and ignoble history, it is only recently that trafficking has become a major political issue for states and the international community and the subject of detailed international rules. Anne T. Gallagher calls on her direct experience working within the United Nations to chart the development of new international laws on this issue.
Keywords: Derecho internacional humanitario; Tráfico de personas